Synthesis and antimicrobial activity of new betulin derivatives - Agata Serrafi; Andrzej Wasilewski (Scientific Reports)
Abstract The overuse and often unjustified application of antibiotics have led to the emergence of drug-resistant bacterial strains, posing a serious threat to public health. This escalating issue underscores the urgent need to discover new antibiotics and explore novel targets for antibacterial therapies. Betulin, a naturally occurring triterpene found abundantly in white birch bark, has attracted attention due to its broad spectrum of biological activities, even at low concentrations. In this study, we synthesized a novel derivative of betulin and evaluated its antibacterial efficacy against various pathogenic bacterial strains. The betulin derivative demonstrated inhibitory effects on the growth of Staphylococcus aureus, and its Minimum Inhibitory Concentration (MIC) was determined. These findings suggest that betulin derivatives hold promise as potential candidates in the fight against antibiotic-resistant infections.